The current and future seasonal geographic distribution of largehead hairtail Trichiurus japonicus in the Beibu Gulf, South China Sea - Xiong, Pengli; Xu, Youwei; Sun, Mingshuai; Zhou, Xingxing; Jiang, Peiwen; Chen, Zuozhi; Fan, Jiangtao (Frontiers in Marine Science, 2023)
Largehead hairtail Trichiurus japonicus is a major commercial fish species in the Beibu Gulf of the northwestern South China Sea. Despite much effort to protect the resource, the current stock is overexploited. As the impacts of climate change unfold globally, seasonal changes in the distribution of largehead hairtail in the Beibu Gulf have not yet been clarified. This study evaluated changes in geographic projections of a maximum entropy model of T. japonicus under different climate-change scenarios in the Beibu Gulf. Maximum entropy models based on mixed layer depth and salinity were projected onto seasonal habitat changes under a current scenario and three different Representative Concentration Pathways (126, 370, 585) for the periods 2040–2050 and 2090–2100. The current geographic distribution results showed variation with seasonality, as the wintering population shifts toward the northeast. Under each of three SSP scenarios, there is higher risk to habitat suitability in the 2090s as compared with that in the 2050s. Under each of the three climate-change scenarios, the disadvantage to the distribution of T. japonicus is greatest in winter, both in the short- and long-term. Potential suitable habitat distributions have a minor range extension in Representative Concentration Pathway 370–2050 winter, but in the rest of the scenes and years they contract to south of the Beibu Gulf. The overall results indicate that seasonal differences in suitable habitat should be considered to ensure effective planning of future management strategies for T. japonicus.